Playing Nabokov: Performances by Himself and Others - Susan Elizabeth Sweeney (Studies in 20th & 21st Century Literature, 1998)
In 1918, in the Crimea, the adolescent Vladimir Nabokov devised a new pastime: "parodizing a biographic approach" by narrating his own actions aloud. In this self-conscious "game," he orchestrated changes in grammatical person, gender, and tense in order to transform his present experiences into a third-person past, as remembered by a female friend in an imaginary future. Staging his own biography in this fashion allowed Nabokov to resolve the inherent conflict between his life and his art. Indeed, he went on to play the game of narrating his own biography throughout his memoir, Speak, Memory: An Autobiography Revisited, and in his fiction. Fifty years after Nabokov invented this game, he met his first real-life biographer, Andrew Field, who resisted playing it by Nabokov's rules. The ensuing quarrel between subject and biographer eventually inspired three other parodic texts: Nabokov's novel, Look at the Harlequins!; Field's biography, Nabokov: His Life in Part, and Roberta Smoodin's novel, Inventing Ivanov. Inevitably, each of these books became, like Speak, Memory before it, another performance of Nabokov's self-reflexive game. Indeed, Nabokov's critics, biographers, and disciples may find it almost impossible to represent his life and art without merely repeating his own representations of himself.
Keywords: 1918; Crimea; adolescent Vladimir Nabokov; adolescent; Vladimir Nabokov; pastime; parodizing a biographic approach; narrating; aloud; self-conscious; game; grammatical person; gender; tense; third-person past; female friend; imaginary future; biography; conflict; life; art; " Speak; Memory: An Autobiography Revisited" Andrew Field; Look at the Harlequins!; Nabokov: His Life in Part; Roberta Smoodin; Inventing Ivanov; self-reflexive game